Effectiveness of Regulatory Policies on Online/Digital/Internet-Mediated Alcohol Marketing: a Systematic Review - Sandra Radoš Krnel; Gorazd Levičnik; Wim van Dalen; Giulia Ferrarese; Sandra Tricas-Sauras (Journal of Epidemiology and Global Health, 2023)
Abstract Background The rapid growth of social networking sites and video sharing platforms has created an opportunity for the alcohol industry to employ advanced advertising and marketing approaches to target their audiences, increasingly blurring the lines between commercial marketing and user-generated content, which poses a challenge for effective regulation. Methods We conducted a systematic search through three peer-reviewed journal databases (WoS, PubMed, Scopus). Studies were included if published in English, after 2004, and assessed statutory regulation or voluntary industry codes, enacted by an EU or nation’s governmental agency or private entity, and with the intent to restrict digital alcohol advertising. In addition, we conducted a manual search of gray literature. Results A total of 4690 records were identified. After duplicate removal and full-text assessment, 14 articles were examined. Our findings indicate that children and adolescents may often be exposed to alcohol advertisements on social media and websites due to industry’s self-regulatory age-affirmation systems being largely ineffective at preventing under-aged access. Cases of self-regulatory violations by the alcohol industry, and increasingly innovative ‘gray-area’ advertising approaches have also been noted. Additionally, research illustrates a lack of developed statutory restrictions of digital alcohol advertising and instead continued reliance on voluntary industry self-regulation. Conclusions There is a substantial need for further research to examine the effectiveness of digital alcohol advertising restrictions in social media, websites and image/video sharing platforms. Moreover, there is a necessity for countries to develop comprehensive statutory frameworks, which would effectively restrict and monitor rapidly advancing digital alcohol advertising practices on new digital media.